A generalized Livestock Gross Margin insurance program for the developing countries. Issue 5 (14th October 2019) - Sun, Yan; Tan, Ken Seng
Abstract : Purpose: The purpose of this paper is to propose a new margin protection (MP) scheme for the producers of hog, cattle and dairy in the developing countries. Design/methodology/approach: The proposed MP scheme is inspired by the Livestock Gross Margin (LGM) program that has been successfully implemented in US directly implementing the LGM program in developing countries can be difficult due to the rudimentary of the futures market with limited futures listing. To address this issue, the authors proxy the futures prices by relating to some relevant spot prices via an econometric model. The proxied futures prices, in turn, enable the implementation of a generalized LGM, which the authors denote as the MP scheme. Findings: As China is the world's largest consumption and production of pork, the authors describe the proposed MP scheme by demonstrating how a generalized LGM can be constructed for the Chinese hog producers. By empirically comparing to the pilot hog price index insurance for the Beijing's hog producers, the authors find that the proposed MP scheme is more effective in providing MP for the producers. Research limitations/implications: The proposed MP scheme still requires the availability of some relevant spot prices in order to use an econometric model to proxy the missing futures prices. Originality/value: The value of this research stems from demonstrating how an MP scheme can be constructed for developing countries that have rudimentary futures markets.